Enhancing Agricultural Practices through ICT: The Diffusion and Impact of the Among Tani Application in Batu City, Indonesia - Alim, Syahirul; Permadi, Angga Sukmara Christian; Firmantoro, Verdy (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2024)
This study examines the implementation and impact of the Among Tani application, a digital platform designed to support farmers in Batu City, Indonesia, as part of a broader smart city initiative. Utilizing a qualitative approach, the research investigates the diffusion process of the application, its role as a virtual communication medium, and its effects on organizational structures within farmer groups. The study reveals a staged adoption process influenced by factors such as farmer age and crop vulnerability. While the application has enhanced access to agricultural information and improved pest management, challenges including the digital divide and integration with traditional practices persist. The findings highlight the complex interplay between digital innovation and existing agricultural systems, emphasizing the need for context-sensitive approaches in implementing agricultural technologies. This research contributes to the understanding of digital agriculture's potential in supporting sustainable rural development and provides insights for future smart city initiatives in agricultural contexts.